Improving Ethanol Permeation Efficiency Using Modified Poly(Vinyl Alcohol) Membrane - Ulfa Andayani; Jumina Jumina; Dwi Siswanta; Diah Mardiana (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2017)
This research is about using blended membrane poly(vinyl alcohol)-pectin that are crosslinked by glutareldehide for ethanol permeation. Poly(vinyl alcohol) or PVA is used as the base membrane, pectin as biopolymers and gluteraldehida (GA) as a crosslinker agent. The objective of this study is improving the efficiency of ethanol permeation using blended PVA membrane with pectin and glutaraldehyde to determine the optimum composition of blended membrane PVA-pectin-GA. Membrane with optimum composition is selected based on the highest flux value. Membrane optimization was obtained by studying the effect of the PVA concentration, the addition of GA and pectin. Moreover, optimization was studied based on membrane permeation rate (flux) of ethanol that passes through the membrane. Membranes with high flux value were selected as the optimum membrane. The results conclude: (1) Addition of gluteraldehide decreased flux values but increased membrane stability. The highest flux value generated from the blended membrane that has cross-linker number (n) 120; (2) Addition of pectin increased flux value but decreased membrane stability. The highest flux value was obtained from blended membrane of PVA-pectin-GA with the optimum composition on mole ratio of PVA: pectin = (1: 2).